Electrophoretic deposition of cobalt oxide anodes for alkaline membrane water electrolyzer. (30th August 2021) - Pozio, Alfonso; Bozza, Francesco; Lisi, Nicola; Mura, Francesco
Summary: Nanostructured cobalt oxide anodes for alkaline membrane electrolysis cell (AME) were fabricated by electrophoretic deposition (EPD) method directly on AISI‐316 sintered metal fiber substrate, and the effect of different amounts of cobalt oxide was evaluated. The influence of the deposition condition on the microstructure and catalytic activity of the anodes was analyzed, showing different characteristics compared to the substrate steel structure. In particular, the catalytic activity for the oxygen evolution reaction (OER) in KOH 0.5 M solution showed an increase depending on the EPD conditions. The composite electrodes were also compared to other materials commonly applied in alkaline electrolysis in order to verify their effective electrocatalytic activity. In particular, the results were compared with electroplated platinum and cobalt with the aim of identifying the better synthesis technique. The results show that the EPD methodology can be adopted to provide an effective method for improving steel anodes of alkaline membrane electrolyzers. Abstract : Nanostructured cobalt oxide anodes for alkaline membrane electrolysis cell (AME) were fabricated by electrophoretic deposition (EPD) method directly on AISI‐316 sintered metal fiber substrate, and the effect of different amounts of cobalt oxide was evaluated. The influence of the deposition condition on the microstructure and catalytic activity of the anodes was analyzed, showing different characteristics compared to the substrate steel structure.